Perbedaan Pengetahuan Remaja Putri tentang Premenstruasi Syndrom Sebelum dan Sesudah Diberikan Pembelajaran Menggunakan Media Gadget - Evin Noviana Sari (Universitas STRADA Indonesia, 2018)
Premenstrual Syndrome (PMS), which is a cycle disorder that is common in young and middle women, is characterized by consistent physical and emotional symptoms, occurring during the luteal phase of the menstrual cycle. This study aims to determine differences in knowledge of young women about premenstrual syndrome before and after being given learning using media gadgets. This study uses an experimental method, which is a study by conducting experimental activities, which aims to find out the symptoms of the effects that arise, as a result of certain treatments with one group pretest-posttest only design.